Impermeable waterproof dry-mixed mortar and preparation method thereof

By adjusting the composition of the dry-mixed mortar and using modified zinc oxide and modified liquid treatment methods, the existing dry-mixed mortar has been solved, and higher mechanical properties and better waterproofing properties are achieved, and its service life is extended.

CN119683934APending Publication Date: 2025-03-25ZHEJIANG LONGYOU TONGQU BUILDING MATERIALS CO LTD

Patent Information

Application Number
CN202411856947.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing high-quality dry-mixed mortar has shortcomings in terms of mechanical properties, impermeability and waterproofing properties, which affects its quality and service life.

Method used

By adjusting the composition of the dry-mixed mortar, the proportion of nano wollastonite powder, fiber reinforcement, anti-seepage agent and waterproofing agent is increased, and the treatment method of modified zinc oxide and modified liquid is adopted to enhance the mechanical properties of the mortar, the anti-seepage and waterproofing properties of the mortar.

Benefits of technology

It significantly improves the mechanical properties, impermeability and waterproof properties of dry-mixed mortar, extends its service life, and improves its quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192091160000091
    Figure BDA0005192091160000091
  • Figure BDA0005192091160000101
    Figure BDA0005192091160000101
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to impermeable waterproof dry-mixed mortar and a preparation method thereof. The impervious waterproof dry-mixed mortar is prepared from the following raw materials in parts by weight: 1400 to 1550 parts of machine-made sand, 380 to 420 parts of Portland cement, 60 to 80 parts of fly ash, 30 to 50 parts of expanded perlite, 10 to 20 parts of latex powder, 7 to 10 parts of sepiolite powder, 5 to 10 parts of nano wollastonite powder, 2 to 4 parts of hydroxyethyl methyl cellulose, 2 to 5 parts of sodium citrate, 10 to 20 parts of fiber reinforcing agent, 3 to 5 parts of impervious agent, 6 to 10 parts of waterproof agent, 2 to 4 parts of expanding agent and 3 to 6 parts of water reducing agent. The dry-mixed mortar prepared by the invention not only has excellent mechanical properties, but also has good impermeability and waterproof performance, and the service life of the dry-mixed mortar is prolonged to a certain extent while the quality of the dry-mixed mortar is effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to an anti-seepage and waterproof dry-mix mortar and a preparation method thereof. Background Art

[0002] Dry mortar, also known as dry mortar, dry-mixed mortar, and dry-mixed powder, refers to a granular or powdered material that is physically mixed in a certain proportion of dried and sieved aggregates (such as quartz sand), inorganic cementitious materials (such as cement), and additives (such as polymers). It is transported to the construction site in bags or bulk and can be used directly after adding water and mixing. Dry mortar has the characteristics of high product quality, full variety, and easy use. In the construction industry, dry mortar plays a bonding, lining, protection and decorative role in thin layers, and is widely used in construction and decoration projects.

[0003] A high-quality dry-mixed mortar and a preparation method thereof are disclosed in a patent document with application number "CN201911162335.2". Provided is a high-quality dry-mixed mortar and a preparation method thereof, belonging to the field of building materials, wherein the high-quality dry-mixed mortar comprises the following components by weight: 300-420 parts of sulphoaluminate cement, 1500-1650 parts of machine-made sand, 90-120 parts of limestone powder, 60-80 parts of bentonite, 60-90 parts of coal slag, 2-5 parts of polycarboxylic acid water reducer containing pyrophosphate group, 0.7-0.9 parts of sulfoalanine, 0.4-0.6 parts of sodium thiosulfate, and 0.6-1.0 parts of silicone defoamer. Although the dry-mixed mortar prepared in this patent document has excellent workability and shrinkage resistance. However, its own mechanical properties are relatively insufficient, and its anti-seepage and waterproof properties are relatively poor, which not only affects its quality to a certain extent, but also shortens its service life. Therefore, the present invention provides an anti-seepage and waterproof dry-mix mortar and a preparation method thereof, aiming to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide an anti-seepage and waterproof dry-mix mortar and a preparation method thereof. The prepared dry-mix mortar not only has excellent mechanical properties, but also has good anti-seepage and waterproof properties, which effectively guarantees its quality while also extending its service life to a certain extent.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A seepage-proof and waterproof dry-mix mortar is composed of the following raw materials in parts by weight: 1400-1550 parts of machine-made sand, 380-420 parts of silicate cement, 60-80 parts of fly ash, 30-50 parts of expanded perlite, 10-20 parts of latex powder, 7-10 parts of sepiolite powder, 5-10 parts of nano-wollastonite powder, 2-4 parts of hydroxyethyl methyl cellulose, 2-5 parts of sodium citrate, 10-20 parts of fiber reinforcement, 3-5 parts of anti-seepage agent, 6-10 parts of waterproofing agent, 2-4 parts of expansion agent and 3-6 parts of water reducing agent.

[0007] Furthermore, the latex powder is selected from any one of polyethylene vinyl acetate, polyvinyl acetate-versatate, and polystyrene-acrylate.

[0008] Furthermore, the preparation method of the fiber reinforcement comprises the following steps:

[0009] Step 1, dripping hydrogen peroxide with a concentration of 25-30wt% into glass fiber with a mass of 3-8% of hydrogen peroxide, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 80-90°C for 4-6h; after the reaction is completed, filtering out the glass fiber, and then washing and drying it in sequence to obtain pretreated glass fiber;

[0010] Step 2: put the pretreated glass fiber into a modification liquid with a mass 10 to 20 times that of the pretreated glass fiber, and then add modified zinc oxide with a mass 0.5 to 0.8 times that of the pretreated glass fiber, mix and stir evenly, and then keep stirring and react at a temperature of 40 to 50° C. for 1 to 2 hours; after the reaction is completed, filter the product components, and obtain the fiber reinforcement after drying the obtained solid filter material.

[0011] Furthermore, the preparation method of the modified liquid is: add 6-10% of 3-aminopropyltrimethoxysilane to 70-80wt% ethanol aqueous solution, mix and stir evenly, and then hydrolyze at 45-55°C for 5-8h; the modified liquid is obtained after the hydrolysis is completed.

[0012] Furthermore, the preparation method of the modified zinc oxide comprises the following steps:

[0013] The first step is to ultrasonically disperse nano zinc oxide in deionized water at a solid-liquid ratio of 20 to 50 g / L, adjust the pH to 6.0 to 6.5, then add vinyl triethoxysilane in an amount of 0.8 to 1.2 times the mass of nano zinc oxide, mix and stir evenly, and then heat and react at a temperature of 80 to 85° C. for 3 to 5 hours;

[0014] Step 2: After the reaction is completed, add 1.5-2 times the mass of nano zinc oxide methacrylic acid, 0.02-0.04 times the mass of ammonium persulfate, and 0.03-0.06 times the mass of sodium bisulfite to the resulting components, mix well, and then keep warm at 85-90°C for 3-5 hours;

[0015] The third step is to separate the solid and liquid components of the product after the reaction is completed, wash the filter cake with anhydrous ethanol and deionized water alternately for 3 to 5 times and then vacuum dry it, and the final product is modified zinc oxide.

[0016] Furthermore, the anti-seepage agent is selected from any one of sodium methyl siliconate, sodium ethyl siliconate, polymethyl acrylate, and polyethyl acrylate.

[0017] Furthermore, the waterproofing agent is selected from any one of Dow Corning SHP-50, Dow Corning SHP-60, Haichuan Technology HF200, Jinfeng Chemical 8851, and Wacker BS1001 waterproofing agent.

[0018] Furthermore, the expansion agent is any one of UEA, CEA, AEA and GNA expansion agents.

[0019] Furthermore, the water reducer is selected from any one of ZH-2A type high-efficiency water reducer, FDN-C type naphthalene-based water reducer, and HT-HPC polycarboxylic acid high-performance water reducer.

[0020] A method for preparing an anti-seepage and waterproof dry-mix mortar comprises the following steps: accurately weighing various raw materials required for preparing the anti-seepage and waterproof dry-mix mortar, then adding various raw materials into a stirring device, and mechanically stirring the mixture to obtain the anti-seepage and waterproof dry-mix mortar.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention firstly disperses nano zinc oxide in deionized water by ultrasonic method, and then adds vinyl triethoxysilane after adjusting pH value, and reacts vinyl triethoxysilane with relevant groups on the surface of nano zinc oxide through heat preservation reaction, and finally successfully introduces unsaturated double bonds on the surface of nano zinc oxide, and then performs modification treatment on nano zinc oxide under the action of ammonium persulfate, and finally obtains modified zinc oxide. Meanwhile, in the present invention, hydrogen peroxide is dripped into glass fiber, and hydroxyl groups are introduced on the surface of glass fiber after heat preservation reaction, so as to obtain pretreated glass fiber. Then, the pretreated glass fiber is put into the modification liquid, and modified zinc oxide is added thereto, and heat preservation and stirring reaction is performed after mixing and stirring evenly, so that the modified zinc oxide is effectively bonded to the surface of glass fiber under the "bridge" action of 3-aminopropyltrimethoxysilane, and a fiber reinforcing agent is prepared. After being treated with hydrogen peroxide, the roughness of the surface of glass fiber is effectively improved, and the roughness of the surface of the fiber reinforcing agent is further increased in combination with the modified zinc oxide bonded on the surface. The fiber reinforcement is used as a raw material for dry-mixed mortar, which can effectively increase the contact surface and friction between the fiber reinforcement and the mortar matrix, and effectively improve the mechanical properties of the dry-mixed mortar. Furthermore, the dry-mixed mortar prepared by the present invention also has excellent anti-seepage and waterproof properties, which effectively guarantees its quality and prolongs its service life to a certain extent. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A waterproof and anti-seepage dry-mix mortar is composed of the following raw materials in parts by weight: 1400 parts of machine-made sand, 380 parts of P·O42.5 cement, 60 parts of fly ash (particle size 700 mesh), 30 parts of expanded perlite, 10 parts of polyethylene vinyl acetate, 7 parts of sepiolite powder, 5 parts of nano-wollastonite powder, 2 parts of hydroxyethyl methylcellulose, 2 parts of sodium citrate, 10 parts of fiber reinforcement, 3 parts of sodium methylsiliconate, 6 parts of Dow Corning SHP-50 waterproofing agent, 2 parts of UEA expansion agent and 3 parts of ZH-2A type high-efficiency water reducing agent; wherein the fineness modulus of the machine-made sand is 1.8, MB is 1.4, and the stone powder content is 10%.

[0026] The preparation method of the fiber reinforcement comprises the following steps:

[0027] Step 1, dripping 25wt% hydrogen peroxide into 3% of its mass glass fiber (length 10mm), mixing and stirring evenly, and then keeping warm at 80°C for 4h; after the reaction is completed, filtering out the glass fiber, and then washing and drying in sequence to obtain the pretreated glass fiber;

[0028] Step 2: put the pretreated glass fiber into a modification liquid with a mass 10 times that of the pretreated glass fiber, and then add modified zinc oxide with a mass 0.5 times that of the pretreated glass fiber, mix and stir evenly, and then keep stirring and react at a temperature of 40°C for 1 hour; after the reaction is completed, filter the product components, and obtain the fiber reinforcement after drying the obtained solid filter material.

[0029] The preparation method of the modified liquid is as follows: add 6% of 3-aminopropyltrimethoxysilane by weight to a 70wt% ethanol aqueous solution, mix and stir evenly, and then hydrolyze at a temperature of 45°C for 5h; after the hydrolysis is completed, the modified liquid is obtained.

[0030] The preparation method of modified zinc oxide comprises the following steps:

[0031] The first step is to ultrasonically disperse nano zinc oxide in deionized water at a solid-liquid ratio of 20 g / L, adjust the pH to 6.0, then add vinyl triethoxysilane with a mass 0.8 times that of nano zinc oxide, mix and stir evenly, and then keep the mixture at 80°C for 3 hours;

[0032] Step 2: After the reaction is completed, add methacrylic acid with a mass of 1.5 times that of nano zinc oxide, 0.02 times that of ammonium persulfate and 0.03 times that of sodium bisulfite to the resulting components, mix well and keep warm at 85°C for 3 hours;

[0033] The third step is to separate the solid and liquid components of the product after the reaction is completed, wash the filter cake with anhydrous ethanol and deionized water alternately for 3 times and then vacuum dry it, and the final product is modified zinc oxide.

[0034] A method for preparing an anti-seepage and waterproof dry-mix mortar comprises the following steps: accurately weighing various raw materials required for preparing the anti-seepage and waterproof dry-mix mortar, then adding various raw materials into a stirring device, and mechanically stirring the mixture to obtain the anti-seepage and waterproof dry-mix mortar.

[0035] Example 2

[0036] The preparation method of an anti-seepage and waterproof dry-mixed mortar provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the anti-seepage and waterproof dry-mixed mortar and the preparation method of the fiber reinforcing agent are not exactly the same. The specific composition of the anti-seepage and waterproof dry-mixed mortar and the preparation method of the fiber reinforcing agent in this embodiment are as follows:

[0037] A waterproof and anti-seepage dry-mix mortar is composed of the following raw materials in parts by weight: 1500 parts of machine-made sand, 400 parts of silicate cement, 70 parts of fly ash, 40 parts of expanded perlite, 15 parts of polyethylene vinyl acetate, 8 parts of sepiolite powder, 8 parts of nano-wollastonite powder, 3 parts of hydroxyethyl methylcellulose, 4 parts of sodium citrate, 15 parts of fiber reinforcement, 4 parts of sodium methyl siliconate, 8 parts of Dow Corning SHP-60 waterproofing agent, 3 parts of CEA expansion agent and 5 parts of FDN-C naphthalene-based water reducer.

[0038] The preparation method of the fiber reinforcement comprises the following steps:

[0039] Step 1, dripping 25wt% hydrogen peroxide into 5wt% glass fiber, mixing and stirring evenly, and then heat-retaining and reacting at 85°C for 5h; after the reaction is completed, filtering out the glass fiber, and then washing and drying in sequence to obtain the pretreated glass fiber;

[0040] Step 2: put the pretreated glass fiber into a modification liquid with a mass 15 times that of the pretreated glass fiber, and then add modified zinc oxide with a mass 0.6 times that of the pretreated glass fiber, mix and stir evenly, and then keep stirring and react at a temperature of 45°C for 2 hours; after the reaction is completed, filter the product components, and obtain the fiber reinforcement after drying the obtained solid filter material.

[0041] The preparation method of the modified liquid is as follows: add 8% of 3-aminopropyltrimethoxysilane by weight to 75wt% ethanol aqueous solution, mix and stir evenly, and then hydrolyze at 50°C for 6h; after the hydrolysis is completed, the modified liquid is obtained.

[0042] The preparation method of modified zinc oxide comprises the following steps:

[0043] The first step is to ultrasonically disperse the nano zinc oxide in deionized water at a solid-liquid ratio of 30 g / L, adjust the pH to 6.0, then add vinyl triethoxysilane in an amount equal to the mass of the nano zinc oxide, mix and stir evenly, and then heat and react at 80°C for 4 hours;

[0044] Step 2: After the reaction is completed, add methacrylic acid with a mass of 1.5 times that of nano zinc oxide, 0.03 times that of ammonium persulfate and 0.05 times that of sodium bisulfite to the resulting components, mix well and keep warm at 85°C for 4 hours;

[0045] The third step is to separate the solid and liquid components of the product after the reaction is completed, wash the filter cake with anhydrous ethanol and deionized water alternately for 4 times and then vacuum dry it, and the final product is modified zinc oxide.

[0046] Example 3

[0047] The preparation method of an anti-seepage and waterproof dry-mixed mortar provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the anti-seepage and waterproof dry-mixed mortar and the preparation method of the fiber reinforcing agent are not exactly the same. The specific composition of the anti-seepage and waterproof dry-mixed mortar and the preparation method of the fiber reinforcing agent in this embodiment are as follows:

[0048] A seepage-proof and waterproof dry-mix mortar is composed of the following raw materials in parts by weight: 1550 parts of machine-made sand, 420 parts of silicate cement, 80 parts of fly ash, 50 parts of expanded perlite, 20 parts of polyethylene vinyl acetate, 10 parts of sepiolite powder, 10 parts of nano-wollastonite powder, 4 parts of hydroxyethyl methylcellulose, 5 parts of sodium citrate, 20 parts of fiber reinforcement, 5 parts of sodium methyl siliconate, 10 parts of Dow Corning SHP-50 waterproofing agent, 4 parts of AEA expansion agent and 6 parts of HT-HPC polycarboxylic acid high-performance water reducing agent.

[0049] The preparation method of the fiber reinforcement comprises the following steps:

[0050] Step 1, dripping 30wt% hydrogen peroxide into 8wt% glass fiber, mixing and stirring evenly, and then heat-retaining and reacting at 90°C for 6h; after the reaction is completed, filtering out the glass fiber, and then washing and drying in sequence to obtain the pretreated glass fiber;

[0051] Step 2: put the pretreated glass fiber into a modification liquid with a mass 20 times that of the pretreated glass fiber, and then add modified zinc oxide with a mass 0.8 times that of the pretreated glass fiber, mix and stir evenly, and then keep stirring and react at a temperature of 50°C for 2 hours; after the reaction is completed, filter the product components, and obtain the fiber reinforcement after drying the obtained solid filter material.

[0052] The preparation method of the modified liquid is as follows: add 10% of 3-aminopropyltrimethoxysilane by weight to 80wt% ethanol aqueous solution, mix and stir evenly, and then hydrolyze at 55°C for 8h; after the hydrolysis is completed, the modified liquid is obtained.

[0053] The preparation method of modified zinc oxide comprises the following steps:

[0054] The first step is to ultrasonically disperse nano zinc oxide in deionized water at a solid-liquid ratio of 50 g / L, adjust the pH to 6.5, then add vinyl triethoxysilane with a mass 1.2 times that of nano zinc oxide, mix and stir evenly, and then keep the mixture at 85°C for 5 hours;

[0055] Step 2: After the reaction is completed, add methacrylic acid with a mass of 2 times that of nano zinc oxide, 0.04 times that of ammonium persulfate and 0.06 times that of sodium bisulfite to the resulting components, mix well and keep warm at 90°C for 5 hours;

[0056] The third step is to separate the solid and liquid components of the product after the reaction is completed, wash the filter cake with anhydrous ethanol and deionized water alternately for 5 times and then vacuum dry it, and the final product is modified zinc oxide.

[0057] Comparative Example: The difference between this comparative example and Example 1 is that an equal amount of glass fiber is used to replace the fiber reinforcement in this comparative example.

[0058] Performance test: According to the JC / T984-2011 "Polymer Cement Waterproof Mortar" standard, the relevant properties of the anti-seepage and waterproof dry-mixed mortar samples prepared in Examples 1 to 3 and the comparative example were tested, and the obtained test data were recorded in the following table:

[0059]

[0060]

[0061] By comparing and analyzing the relevant data in the table, it can be seen that the dry-mixed mortar prepared by the present invention not only has excellent mechanical properties, but also has good anti-seepage and waterproof properties, which effectively guarantees its quality and prolongs its service life to a certain extent. This shows that the anti-seepage and waterproof dry-mixed mortar and its preparation method provided by the present invention have a broader market prospect and are more suitable for promotion.

[0062] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0063] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An anti-seepage and waterproof dry-mix mortar, characterized in that: The invention is composed of the following raw materials in parts by weight: 1400-1550 parts of machine-made sand, 380-420 parts of silicate cement, 60-80 parts of fly ash, 30-50 parts of expanded perlite, 10-20 parts of latex powder, 7-10 parts of sepiolite powder, 5-10 parts of nano-wollastonite powder, 2-4 parts of hydroxyethyl methyl cellulose, 2-5 parts of sodium citrate, 10-20 parts of fiber reinforcement, 3-5 parts of anti-seepage agent, 6-10 parts of waterproofing agent, 2-4 parts of expansion agent and 3-6 parts of water reducing agent.

2. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The latex powder is selected from any one of polyethylene vinyl acetate, polyvinyl acetate-versatate vinyl ester, and polystyrene-acrylate.

3. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The preparation method of the fiber reinforcement comprises the following steps: Step 1, dripping hydrogen peroxide with a concentration of 25-30wt% into glass fiber with a mass of 3-8% of hydrogen peroxide, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 80-90°C for 4-6h; after the reaction is completed, filtering out the glass fiber, and then washing and drying it in sequence to obtain pretreated glass fiber; Step 2: put the pretreated glass fiber into a modification liquid with a mass 10 to 20 times that of the pretreated glass fiber, and then add modified zinc oxide with a mass 0.5 to 0.8 times that of the pretreated glass fiber, mix and stir evenly, and then keep stirring and react at a temperature of 40 to 50° C. for 1 to 2 hours; after the reaction is completed, filter the product components, and obtain the fiber reinforcement after drying the obtained solid filter material.

4. The anti-seepage and waterproof dry-mix mortar according to claim 3, characterized in that: The preparation method of the modified liquid is as follows: add 6-10% of 3-aminopropyltrimethoxysilane to 70-80wt% ethanol aqueous solution, mix and stir evenly, and then hydrolyze at 45-55°C for 5-8h; after the hydrolysis is completed, the modified liquid is obtained.

5. The anti-seepage and waterproof dry-mix mortar according to claim 3, characterized in that: The preparation method of the modified zinc oxide comprises the following steps: The first step is to ultrasonically disperse nano zinc oxide in deionized water at a solid-liquid ratio of 20 to 50 g / L, adjust the pH to 6.0 to 6.5, then add vinyl triethoxysilane in an amount of 0.8 to 1.2 times the mass of nano zinc oxide, mix and stir evenly, and then heat and react at a temperature of 80 to 85° C. for 3 to 5 hours; Step 2: After the reaction is completed, add 1.5-2 times the mass of nano zinc oxide methacrylic acid, 0.02-0.04 times the mass of ammonium persulfate, and 0.03-0.06 times the mass of sodium bisulfite to the resulting components, mix well, and then keep warm at 85-90°C for 3-5 hours; The third step is to separate the solid and liquid components of the product after the reaction is completed, wash the filter cake with anhydrous ethanol and deionized water alternately for 3 to 5 times and then vacuum dry it, and the final product is modified zinc oxide.

6. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The anti-seepage agent is selected from any one of sodium methyl siliconate, sodium ethyl siliconate, polymethyl acrylate and polyethyl acrylate.

7. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The waterproofing agent is selected from any one of Dow Corning SHP-50, Dow Corning SHP-60, Haichuan Technology HF200, Jinfeng Chemical 8851, and Wacker BS1001 waterproofing agent.

8. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The expansion agent is any one of UEA, CEA, AEA and GNA expansion agents.

9. The anti-seepage and waterproof dry-mix mortar according to claim 1, characterized in that: The water reducer is selected from any one of ZH-2A high-efficiency water reducer, FDN-C naphthalene-based water reducer and HT-HPC polycarboxylic acid high-performance water reducer.

10. The method for preparing anti-seepage and waterproof dry-mix mortar according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: accurately weighing various raw materials required for preparing anti-seepage and waterproof dry-mixed mortar, then adding various raw materials into a stirring device, and mechanically stirring the mixture to obtain the anti-seepage and waterproof dry-mixed mortar.

Citation Information

Patent Citations

  • High-quality dry-mixed mortar and preparation method thereof

    CN110818369A

Cited By

  • High-strength anti-cracking dry-mixed plastering mortar and preparation process thereof

    CN120607393A

  • A high-strength, crack-resistant dry-mix plastering mortar and its preparation process

    CN120607393B

  • Anti-crack concrete and preparation method thereof

    CN121573949A

  • A crack-resistant concrete and its preparation method

    CN121573949B